The Impact of Going Concerns on the Financial Reporting Quality of Listed Firms on the Vietnam Stock Market - Thu, Phung Anh; Khuong, Nguyen Vinh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 3, 2018)
The investigation was conducted to contribute empirical evidence of the association between going concerns and the financial reporting quality of listed firms on the Vietnam stock market. Based on the data of 279 companies listed on the HNX and HOSE exchanges in Vietnam in the 2009-2015 period, through quantitative research, that the relationship between the going concerns and the financial reporting quality of the listed firms was found. The research results are significant for investors, regulators for the transparency of financial reporting information.